Systematic analysis of spontaneous tandem genome amplification events in Yersinia pestis - Dmitry N. Konanov; Olga N. Liubimova; Alexander V. Kovrizhnikov; Ignat V. Sonets; Alina N. Balykova; Alexandra V. Lukina-Gronskaya; Anna S. Speranskaya; Danil V. Krivonos; Galina A. Eroshenko; Elena N. Ilina; Vadim M. Govorun; Vladimir V. Kutyrev (PLoS ONE, 2025)
Tandem amplification of genomic fragments is quite common in bacteria growing under stress conditions, while spontaneous genome amplification events are rare, unstable and generally poorly described. Plague pathogen Yersinia pestis is a unique microorganism that contains an enormous number of short repeat sequences in its genome and as a result is very prone to spontaneous genome rearrangements including large tandem genome amplification events. Eleven Y. pestis strains sequenced during this study and more than thousand read archives from SRA were analyzed in this study. It was shown that genomes of more than half of Y. pestis laboratory isolates contain tandem repeats. They are mainly caused by the presence of multicopy IS-elements but a few of them are associated with multicopy rRNA clusters, so the rearrangement mechanism is most likely RecA-dependent recombination. Four regions with unstable copy number reproduced between different bioprojects were found. One of them was identified as an integrative mobilizable element carrying a probably incomplete Type 4 secretion system. More interesting, two other reproducible regions were not identified as mobile elements but had the length and GC-content almost identical to the length and GC-content of pMT1 and pCD1 plasmids.